BUSINESS MODEL OF GAMING PLATFORMS: Redefining Atari Business Model - Annanmäki, Juha (My University, 2014)
Video games have emerged, due to technology development, as one of the biggest forms of entertainment industry in the world today. Despite this, core of the video game industry has remained the same for a long time. This paper will discuss those software platforms used in the video game industry and business models those owners use. Purpose of this study is to provide a business perspective to software platforms and their use in the video game industry. This study was carried out by studying periodicals and academic literature dealing with the software and business platforms of the video game industry and in general. Therefore this is considered to be as an evaluative case study. The research method used was content analysis to identify business models used on industry’s software platforms. The video game industry has experienced some changes due to the development of technology and the popularity of the internet. Two of the biggest changes are increasingly utilized multichannel distribution model and service model. These changes have increased the pressure to develop business models, which is why the current situation is in need for mapping. Presented here is the summary of software platform business models used in the video game industry.
Keywords: Atari; Business Models; Platforms; Ecosystems; fi=Tietotekniikka (KTM)|en=Computer Science|; fi=Multimediajärjestelmien ja teknisen viestinnän koulutusohjelma|en=Multimedia Systems and Technical Communication|